Faculty Actions that Result in Student Satisfaction in Online Courses - Jackson, Lana C; Jones, Stephanie J; Rodriguez, Roy C (Online Learning, 2010)
This study identified faculty actions which positively influenced student satisfaction in the online classroom at the community college level. The escalating demand for Internet-based, distance education courses has been met by an increased inventory of them. However, while online education has been in existence for over a decade, standardized practices in the online classroom have not been fully identified, developed, and implemented. Data was collected from student evaluations of web-based courses at two Texas community colleges. Descriptive statistics, bivariate correlations and multiple regressions were used to identify faculty behaviors which affected the satisfaction of students enrolled in these courses. The results of the study indicated that faculty actions within online courses appeared to impact student satisfaction. The identification of faculty actions which impact student satisfaction in online courses will greatly assist colleges and universities in strengthening their abilities to provide quality online experiences for their students.